Extract Formulation of Zingiber officinale and Phylanthus reticulatus Induces Apoptosis of WiDr Colon Cancer Cells - Kristiani, Elizabeth Betty Elok; Kasmiyati, Sri; Martono, Yohanes; Kachingwe, Baxter Hepburn (Biosaintifika: Journal of Biology & Biology Education, 2025)
People use ginger (Zingiber officinale) extensively for health purposes. Our previous studies have shown that Phyllanthus reticulatus has strong antioxidant capabilities. This study investigates the anticancer potential of ethanolic extract of Z. officinale and P. reticulatus formulations (ZP), focusing on their cytotoxicity and mechanisms against cancer cells. Samples were extracted using the maceration method. The method for determining the cytotoxicity of cells is MTT, the cell cycle is flow cytometry, apoptotic cells are flow cytometry and double staining, and caspase-8 and caspase-9 expression using the immunocytochemistry method. The analysis of caspase-8 and caspase-9 expression using the immunocytochemistry method. Among the tested formulations, the ethanolic extract of ZP_1:0 showed the most promise against WiDr colon cancer cells (IC50 value of 102.1 µg/ml). The ZP_1:0 demonstrated dose-dependent apoptosis induction in WiDr cells, showing early and late apoptosis, with minimal necrosis. The extract activates extrinsic and intrinsic apoptotic pathways in inducing cancer cell death. Compared to doxorubicin, the ZP 1:0 formulation selectively promotes apoptosis with reduced necrotic damage, suggesting the potential for reduced systemic toxicity. The study supports the potential of Z. officinale as a source of safer, plant-based anticancer agents, particularly for colon cancer, while recommending further research to identify and enhance active compounds.